Constitutionally Protected Free Speech: Editor: Thomas H. Sawyer. Issue 5 (12th June 2020) - Sawyer, Tonya L.
Abstract : This case raises the question of whether a public school can lawfully remove a student from an extracurricular activity for her profanity, transmitted off school grounds on a Saturday to fellow students.